2011
DOI: 10.1186/1471-2334-11-266
|View full text |Cite
|
Sign up to set email alerts
|

The molecular epidemiology of circulating rotaviruses: three-year surveillance in the region of Monastir, Tunisia

Abstract: BackgroundRotavirus infection is the most common cause of severe, dehydrating, gastroenteritis among children worldwide. In developing countries, approximately 1440 children die from rotavirus infections each day, with an estimated 527,000 annually. In infants, rotavirus is estimated to cause more than 2 million hospitalizations every year depending on the income level of the country.The purpose of this study was to estimate the proportion of rotavirus gastroenteritis and identify the distribution of circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
6
28
0
Order By: Relevance
“…The summation of those G1, G2, G3, and G9 genotypes accounted for 94.8% in all G genotype in this study, this result was also similar to the other study conclusion, where the total of G1, G2, G3, and G9 accounted over 85% in all RVA strains in China [Li et al, ]. P[8] genotype accounted for 92.8% in all RVA strains in this study, and summation of P[8] and P[6] genotype reached 95% of all P genotype, this conclusion kept with the result of other study conducted in China, which suggested that P[8] was persistent predominant genotype from 1980 to now [Liu et al, ], similar conclusion was that P[8] (80.8%) was characterized as predominant P genotype from 2007 to 2010 in Tunisia [Hassine‐Zaafrane et al, ].…”
Section: Discussionsupporting
confidence: 90%
“…The summation of those G1, G2, G3, and G9 genotypes accounted for 94.8% in all G genotype in this study, this result was also similar to the other study conclusion, where the total of G1, G2, G3, and G9 accounted over 85% in all RVA strains in China [Li et al, ]. P[8] genotype accounted for 92.8% in all RVA strains in this study, and summation of P[8] and P[6] genotype reached 95% of all P genotype, this conclusion kept with the result of other study conducted in China, which suggested that P[8] was persistent predominant genotype from 1980 to now [Liu et al, ], similar conclusion was that P[8] (80.8%) was characterized as predominant P genotype from 2007 to 2010 in Tunisia [Hassine‐Zaafrane et al, ].…”
Section: Discussionsupporting
confidence: 90%
“…This distribution was different from the seasonality of human rotaviruses, which peaked in winter (Hassine‐Zaafrane et al . ). A study conducted in Japan on healthy calves showed that the highest detection rate of rotavirus genes was in January followed by December (Abe et al .…”
Section: Discussionmentioning
confidence: 97%
“…The viral RNA was extracted as previously described (Hassine‐Zaafrane et al . ) and then was analysed using one‐step RT‐PCR kit (QIAGEN, Hilden, Germany) and primers amplifying partial VP6 gene (Iturriza‐Gomara et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Rotavirus infections were essentially recovered during the coldest months, as described elsewhere (Benhafid et al 2013), even in the same geographical area (Hassine-Zaafrane et al, 2011). Rotavirus was the most frequent virus involved in the development of cases of diarrhoea, and ranking as the specific second cause of diarrhoea after EAEC isolates.…”
Section: Aetiology Of Diarrhoea In Moroccomentioning
confidence: 97%
“…Although some data on the aetiological causes of diarrhoea in some North African countries are available (Al-Gallas et al, 2007;Hassine-Zaafrane et al, 2011SdiriLoulizi et al, 2009SdiriLoulizi et al, , 2011, little is known about the aetiology and epidemiology of diarrhoea in Morocco. The latest estimates suggest that diarrhoea may be responsible for the death of 36 per 1000 live births annually in Morocco (UNICEF/WHO, 2009).…”
Section: Introductionmentioning
confidence: 99%